Pengaruh Kualitas Pelayanan E-Channel dan Kualitas Pelayanan Tatap Muka Terhadap Kepuasan dan Loyalitas Penabung (Studi Pada Bank Kalsel di Kabupaten Barito Kuala) - Deni Deni; Saladin Ghalib (Universitas Lambung Mangkurat, 2023)
The research method used is positivistic, descriptive/explanatory causality, data collection using a survey method with a sample size of 648 Simpeda General savers and Simpeda KPE savers selected by multistage proportional convenience sampling technique. The google form questionnaire was distributed via whatsapp group and 400 copies were printed. The 676 copies of the questionnaire that returned after being verified were selected as many as 648 copies according to the initial plan. Data analysis using path analysis technique, data calculation using SPSS Version 25 application.The results of the study found that the quality of e-channel services had a significant positive effect on both satisfaction and customer loyalty. The quality of face-to-face services has a significant positive effect on both satisfaction and customer loyalty. Satisfaction has a significant positive effect on the loyalty of savers. Satisfaction mediates the significant positive effect of E-Channel service quality on saver loyalty. Satisfaction also mediates the positive effect of face-to- face service quality on saver loyalty. The results of this study are useful as a basis for managing decisions to increase saver loyalty through efforts to improve service quality (e-channel and face-to-face) in the context of increasing saver satisfaction at this bank. Keywords: Loyalty, Satisfaction, Service Quality, e-channel, face-to-face, savers